Citation typologies and rhetorical functions of citations in master dissertations / Nik Mastura Nik Ismail Azlan - Nik Ismail Azlan, Nik Mastura (Universiti Teknologi MARA Cawangan Kedah, 2013)
This study compares the use of citation typologies and the rhetorical citation functions in three M. Ed TESL and three M. Ed Visual Art Education dissertations in the field of education. Document analysis was conducted to identify the types of citations used (integral or non-integral citations) in the Introduction, Literature Review, Methodology, and Results and Discussion sections. The use of integral citations was found to be more frequent than non-integral citations for both M. Ed TESL and M. Ed Visual Art Education dissertations. In addition, the ‘Literature Review’ contained the highest density of citations in both M. Ed TESL and M. Ed Visual Art Education dissertations. Citations identified in the corpus were also coded in terms of rhetorical functions. ‘Attribution’ was found to have the highest density in both M. Ed TESL and M. Ed Visual Art Education dissertations. However, repetitive occurrence of ‘incorrect use of citations’ was found in some of the dissertations. In conclusion, the paper argues that lecturers should provide more instruction on various types of citations as well as rhetorical functions of citations in the classroom to enhance students’ writing skills in producing quality academic papers.